TRANSFORMASI PEMIKIRAN PENDIDIKAN ISLAM MENUJU STANDAR INTERNASIONAL: TANTANGAN DAN PELUANG - Faiz Akmal Baihaqi; M.Khoirul Muttaqin; Bagas Bima Sena; Moh.Nur Fauzi (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2025)
Abstract The transformation of Islamic education thought towards international standards has become an increasingly relevant topic in the era of globalization. This research aims to analyze the challenges and opportunities in the effort to harmonize Islamic education with global education standards, without erasing the identity and values of Islam. The research method used is library research with a qualitative-descriptive approach. Data sources come from academic literature, journals, and educational policies of Islamic education in various countries. The results of the research show that the main challenges in this transformation include curriculum differences, language barriers, cultural resistance, and resource limitations. However, there are significant opportunities such as increasing international cooperation, the use of technology in learning, and the integration of Islamic knowledge with modern science. The discussions in this research highlight the importance of an adaptive approach in adopting international standards without neglecting the distinctive characteristics of Islamic education. In addition, curriculum innovation, improving the quality of educators, and utilizing digital technology are important aspects of this transformation. In conclusion, Islamic education needs to develop a flexible and globally competency-based education model, while still rooted in Islamic values. With the right strategies, Islamic education can contribute to building an inclusive world civilization oriented towards the welfare of humanity. Keywords: Islamic Education, transformation, international standards, challenges, opportunities.